AUTOMEDICAÇÃO E MARKETING FARMACÊUTICO: A INFLUÊNCIA DA PUBLICIDADE NA VENDA DE MEDICAMENTOS SEM PRESCRIÇÃO (REMUNOM, 2025)
AbstractThis study analyzed the influence of pharmaceutical marketing on self-medication practices, focusingon the advertising of over-the-counter drugs and its impact on public health. The objective was tounderstand how marketing strategies encourage the indiscriminate consumption of pharmaceuticals,leading to risks such as intoxication, chemical dependence, and drug resistance. The research wasbased on a bibliographic review of scientific articles and recent academic studies, evaluating therelationship between pharmaceutical advertising and its influence on the sale of medications withoutmedical prescription. The results indicated that persuasive advertising campaigns, broadcastedthrough digital, television, and print media, emphasize the benefits of medications while downplayingtheir risks, creating a false sense of security. Furthermore, the ease of access to over-the-counterdrugs reinforces the habit of self-medication, often without proper professional guidance. It isconcluded that the regulation of drug advertising should be improved to ensure more balanced andtransparent information, combined with strengthening the role of pharmacists as key agents inpromoting the rational use of medicines.Keywords: Self-medication; Pharmaceutical Marketing; Drug Advertising.